Are Robots Stealing Our Jobs? - Gabriele Pellegrino; Mariacristina Piva; Marco Vivarelli (Institute of Labor Economics (IZA), 2017)
In this work, we test the employment impact of distinct types of innovative investments using a representative sample of Spanish manufacturing firms over the period 2002-2013. Our GMM-SYS estimates generate various results, which are partially in contrast with the extant literature. Indeed, estimations carried out on the entire sample do not provide statistically significant evidence of the expected labor-friendly nature of innovation. More in detail, neither R&D nor investment in innovative machineries and equipment (the so-called embodied technological change, ETC) turn out to have any significant employment effect. However, the job-creation impact of R&D expenditures becomes highly significant when the focus is limited to the high-tech firms. On the other hand and interestingly ETC exhibits its labor-saving nature when SMEs are singled out.
Keywords: O33; 330; innovation; R&D; embodied technological change; employment; GMM-SYS